Rancang Bangun Sistem Informasi Perencanaan Kebutuhan Bahan Baku Pada UMKM Sepatu dan Sandal Suroso - Apriliana, Cahya; Widodo, Arifin Puji; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Micro, small and medium enterprises (SMEs) Shoes and slippers Suroso are owned by individuals and companies engaged in manufacturing producing shoes and sandals in accordance with customer orders ( job order ). During this time, companies often have the delay time of fulfillment of customer orders. This is because in determining the time of the fulfillment of the order is still based on an estimate of the operational part, there’s no checking  the detail about the structure of the product and checking raw materials is not done on a regular basis so it can also lead to a deficiency or excess of raw materials.Based on these problems, was made of information system planning raw material requirement by using the method of Lot For Lot. In the system there are have a few process which is process of receive the ordered, preparation of BOM (Bill Of Material), preparation of BOO ( Bill Of Operation), the initial raw material supplies, create MPS (Master Production Schedule), and the process of MRP (Material Requirement Palnning). In the process of MRP there is namely the process Netting, Lotsizing, Offsetting dan Exploding. In the system have few process namely process of receive the order, preparation of BOM (Bill Of Material), preparation of BOO ( Bill Of Operation), record the initial raw material supplies, create MPS (Master Production Schedule), and the process of MRP (Material Requirement Palnning). In the process of MRP namely the process Netting, Lotsizing, Offsetting dan Exploding.The system information made to produce the report of raw material requirement plan, report of the plan production and report of raw material purchase plan. In addition the system also generate report of orders per period, customer report most often conduct transactions and report the most product ordered. Based on the information system is created and a series of trials that have been conducted , the company can find information needed especially concerning raw material such as what are the raw materials must be reserved , how many and when raw materials must be ordered.